Pola Pikir Masyarakat Asli Papua Dalam Peningkatan Daya Saing Perekonomian - Dewi Putri Anjar Wulan; Irfan Wildzan Muafa (Universitas Musamus,Merauke,Papua, 2020)
This study aims to find out how the mindset of indigenous Papuans in improving economic competitiveness in Kampung Kumbe, what causes their mindsets to be different from migrant communities so that migrants have a higher economic level than the indigenous Papuans in Kampung Kumbe while the assistance is provided by the government has been divided evenly in the village. And to find out the competitiveness of indigenous Papuans with migrant communities. The research approach in this proposal is a descriptive qualitative method that is useful for analyzing the events that occur when the research takes place later with data analysis techniques in the form of data reduction, data presentation, and the conclusion stage or data verification. The results obtained after interviewing 20 respondents, namely the form of the mindset of indigenous Papuans in Kampung Kumbe have a consumptive mindset in which they only emphasize will rather than needs so that economic competitiveness is low.